Study of Class IV Arabic Textbooks at Madrasah Ibtidaiah: Curriculum and Content Perspectives - Hakiki Rikza Irnaini Al Badri; Afifah Shofia Faradisa; Muhammad Farhan; Slamet Daroini (Kitaba, 2023)
In a research study that researchers carried out regarding the study of Arabic textbooks for class IV Madrasah Ibtidaiah by "Jauhar Ali" from the perspective of curriculum and content. This study uses a literature method with a qualitative descriptive approach because, in this research, the researcher will explain in depth the content analysis of the Arabic language textbook for class IV Madrasah Ibtidaiah by Jauhar Ali. The results of the study demonstrate that the textbook was very much in line with KMA 183 in 2019; this is evidenced by the suitability of the objectives of Arabic subjects in KMA 183 in 2019 with the contents of the Arabic language textbook for class IV Madrasah Ibtidaiah by Jauhar Ali. The contents of the Arabic language textbook for class IV MI are very in line with socio-cultural aspects, psychological aspects, as well as linguistic and educational aspects; this can be seen from the contents of the textbooks, be it dialog (hiwar), (reading) qiraah texts or others that contain values—social and culture of the local community as well as the religion of Islam. In addition, the Arabic language textbook for grade IV Madrasah Ibtidaiah is very suitable for use by children who are in grade IV or aged ten years because it is very well designed and attractive, and the materials in the Arabic textbook for grade IV Madrasah Ibtidaiah begin from easy to more difficult themes.